Circulating malondialdehyde level in patients with epilepsy: A meta-analysis. (July 2022) - Sun, Huaiyu; Li, Jiaai; Maimaiti, Buajieerguli; Liu, Jiayu; Li, Zhaoran; Cheng, Yu; Zhao, Weixuan; Mijiti, Salamaitiguli.; Jiang, Ting; Meng, Qian; Wang, Jiangping; Jin, Qi; et al.
Highlights: The first meta-analysis of circulating malondialdehyde levels in epilepsy patients and healthy controls. Malondialdehyde levels are significantly higher in epilepsy patients than in healthy controls. Malondialdehyde may be a reliable marker for oxidative stress in epilepsy patients. Abstract: Purpose: Malondialdehyde (MDA) is an oxidative stress marker that determines the impact of oxidation on MDA levels in patients with epilepsy (PWE) and healthy controls. Methods: A meta-analysis was performed on 15 published studies. A total of 559 PWE and 853 healthy controls were included to evaluate the MDA levels in erythrocytes, serum, and plasma, respectively. Results: Meta-analysis showed that MDA levels were significantly higher in PWE than in healthy controls. Moreover, the meta-analysis demonstrated that MDA levels were increased in three subgroups of serum, plasma, and red blood cells from epileptic patients compared with the control group. Differentiating the subgroups according to the proportion of female patients, region, and MDA detection method showed that MDA levels in epileptic patients were higher than in healthy controls. In addition, MDA levels were significantly higher in the Asian subgroup than in the non-Asian subgroup. There was no potential publication bias. The age of the patients, the proportion of female patients, the region, and methods for measuring MDA of the included studies did not cause heterogeneity. Conclusion: Our results showed increased MDA levels in erythrocytes, serum, and plasma in PWE, which may be an indicator of oxidative damage in epilepsy. This is the first meta-analysis of circulating MDA levels in PWE and healthy controls.